Low temperature synthesis of magnetite and maghemite nanoparticles - Bhagwat, Shrikant; Singh, Hema; Athawale, Anjali; Hannoyer, Beatrice; Jouen, Samuel; Lefez, Benoit; Kundaliya, Darshan; Pasricha, Renu; Kulkarni, Shailaja; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2007)
We report on the synthesis of iron oxide nanoparticles below 100 degrees C by a simple chemical protocol. The uniqueness of the method lies in the use of Ferrous ammoniurn sulphate (in conjugation with FeCl3) which helps maintain the stability of Fe-2+ state in the reaction sequence thereby controlling the phase formation. Hexamine was added as the stabilizer. The nanoparticles synthesized at three different temperatures viz, 5 degrees, 27 degrees, and 95 degrees C are characterized by several techniques. Generally, when a mixture of Fe3+ and Fe2+ is added to sodium hydroxide, alpha-Fe2O3 (the anti-ferromagnetic phase) is formed after the dehydration process of the hydroxide. In our case however, the phases formed at all the three temperatures were found to be ferro (ferri) magnetic, implying modification of the formation chemistry due to the specifics of our method. The nanoparticles synthesized at the lowest temperature exhibit magnetite phase, while increase in growth temperature to 95 degrees C leads to the maghemite phase.
Keywords: low temperature synthesis; maghemite; magnetite; Nanoparticles

Chemical inhomogeneity and mixed-state ferromagnetism in diluted magnetic semiconductor Co : TiO2 - Ogale, Satishchandra B.; Kundaliya, Darshan; Mehraeen, Shareghe; Fu, Lian-feng; Zhang, Shixiong; Lussier, Alexandre; Dvorak, Joe; Browning, Nigel D.; Idzerda, Yves; Venkatesan, Thirumalai (Chemistry of Materials, 2008)
Diluted magnetic semiconductors (DMS) are among the most intensely investigated materials in recent times in view of their great application potential. Yet, they are also the most controversial because of the possibility of extrinsic effects attributable to dopant solubility and clustering, point defects, incorporation of unintentional impurities, etc. This has highlighted the central role of materials chemistry in rendering a specific microstate and property response. In this work, we provide a combined window of high-resolution scanning transmission electron microscopy and electron energy-loss spectrometry, X-ray absorption (XAS)/X-ray magnetic circular dichroism (XMCD), and magnetization measurements on epitaxial rutile CoxTi1-xO2 (x = 0-0.06) system (the first discovered oxide-DMS, which continues to be controversial) grown at low temperature (400 degrees C) under different ambient atmospheres. The study brings out a mixed-state scenario of ferromagnetism involving intrinsic DMS (uniform dopant distribution at low dopant concentration) and coupled cluster magnetism, involving cobalt associations within the matrix at higher concentrations. We also show that by matrix valence control during growth, it is possible to realize a uniform embedded cluster state and the related coupled cluster magnetism.

Co : CdS diluted magnetic semiconductor nanoparticles: radiation synthesis, dopant-defect complex formation, and unexpected magnetism - Bogle, Kashinath A.; Ghosh, Saurabh; Dhole, Sanjay D.; Bhoraskar, Vasant N.; Fu, Lian-feng; Chi, Miao-Fang; Browning, Nigel D.; Kundaliya, Darshan; Das, Gour P.; Ogale, Satishchandra B. (Chemistry of Materials, 2008)
Incorporating a dopant into a nanoparticle is a nontrivial proposition in view of the size dependent surface versus bulk energy considerations and the intrinsic proximity of the surface to the interior, which facilitates migration to the surface. If realized and controlled, however, it can open up new avenues to novel nanomaterials. Some previous studies have shown the dopability of nanosystems but only with specific surface functionalization. Here, we demonstrate the successful dopant incorporation via a new route of pulsed high energy electron induced synthesis. We choose a system Co:CdS (dilutely cobalt doped cadmium sulfide) in view of the well-known application-worthy properties of CdS and the potential possibility of its conversion to a diluted magnetic semiconductor of interest to spintronics. By using various techniques, we show that matrix incorporation and uniform distribution of cobalt are realized in US nanocrystals without the need for additional chemical or physical manipulation. Optical and photoluminescence properties also support dopant incorporation. Interestingly, although magnetism is realized, it is weak, and it decreases at higher cobalt concentration. First principle density functional calculations are performed to understand this counterintuitive behavior. These calculations suggest that the introduction of parent cation or anion vacancies lead to magnetic moment reduction, albeit marginally. However, with some Co impurity fraction in the octahedral interstitial site inside the wurtzite cage, the magnetic moment drops down drastically. This study reveals that defect states may have an interesting role in dopant stabilization in nanosystems, with interesting system dependent consequences for the properties.